The remnant of medieval Christian attitudes towards prophet Muhammad: a critical evaluation of Margoliouth’s pathological theory - Akilu, Muhammad Aliyu; Abdul Rahim, Adibah (University of Malaya, 2019)
The emergence and expansion of Islam have been considered a severe challenge to Christianity. With its significant expansion, the Christians became so much exasperated. Thus, they started searching for every possible avenue to do away with it. In medieval period, many intellectual and military attacks were launched against Islam. One of the strategies was to create false theories which portrayed Prophet Muhammad (p.b.u.h) negatively. The most absurd theory was ‘pathological theory’ which attempted to charge him of being epileptic. Although many attempts have been made by both Muslim and some less biased Christian scholars to fish this theory out from the scene, it continues to have relevance even in some of the well-learned contemporary Christian scholar’s writings. This study attempts to analyse and evaluate David Samuel Margoliouth’s views on this theory since he is one of the well-versed and contemporary Christian scholars. In doing so, analytical, comparative and evaluative approaches have been adopted. The study found that Margoliouth’s argument that the Prophet (p.b.u.h) suffered from epilepsy was false and baseless. If the experience of the Prophet (p.b.u.h) was said to be the sign of epilepsy, then the biblical Prophets must also face the same charge since they shared the same physical experiences with the Prophet (p.b.u.h).